Students’ Learning Approaches in The EFL Emergency Online Learning Context - Made Hery Santosa; Ni Made Ratminingsih; Luh Diah Surya Adnyani (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2021)
Emergency online learning has transformed today’s learning while opening up opportunities and challenges, one of which is learning approach. This study aims to investigate students’ learning approach in the English Education study program in emergency online learning. A mixed-method was employed using two instruments; R-SPQ-2F questionnaire and semi-structured interviews. The results of the instrument check showed that the R-SPQ-2F survey and interview guide were valid (.90) and reliable (α=.88). Calculated using Slovin formula, there were 302 respondents for this study. The survey data were analysed using R-SPQ-2F mean score analysis and interview data were with interactive model analysis. The results of the study indicate that the learning approach of students in the English education study program in the context of emergency learning tends to be deep. The interview results provide important information that the student approach is influenced by several supporting and inhibiting factors. This shows that the student learning approach is dynamic in adjusting to learning process. Policy makers, lecturers, and students need to consider aspects of this learning approach in the current emergency online situation for a more effective and meaningful learning process.